Real-World Treatment for Menopausal Symptoms in the U.S. by Practitioner Type [A133]. (May 2022) - DePree, Barbara; Houghton, Katherine; Shiozawa, Aki; Esterberg, Elizabeth; Kim, Janet; Mancuso, Shayna
Abstract : INTRODUCTION: Vasomotor symptoms are the most common menopausal symptoms for which women seek treatment. We describe current treatment use by practitioner type (gynecologists versus primary care providers [PCPs]) and U.S. geographic region. METHODS: This subgroup analysis of a noninterventional, observational study used a convenience sample of 283 practitioners (131 gynecologists, 152 PCPs) who abstracted data on menopause-specific therapy from medical records of women aged 40‒60 years who initially presented with menopausal symptoms between January 1, 2016, and December 31, 2019. Data were summarized descriptively. RESULTS: Practitioners provided data for 1, 016 women (from gynecologists: 512; PCPs: 504). About half the women overall experienced symptoms for ≥6 months before consultation. Patients of gynecologists had more vaginal and sexual symptoms recorded than patients of PCPs. Gynecologists' patients more commonly had prescription medications (63% versus 57%) but less commonly had nonprescription therapies/interventions (59% versus 66%) documented than PCPs' patients. They more often received hormone therapy (HT; 76% versus 64% of patients with any prescription) and compounded HT (17% versus 7%) and less often received selective serotonin reuptake inhibitors (SSRIs; 11% versus 19%) and serotonin-norepinephrine reuptake inhibitors (2% versus 12%) than PCPs' patients. Black cohosh was the most frequently documented nonprescription therapy by gynecologists (24%) and PCPs (35%); gynecologists more commonly documented Estroven (16% versus 10%). Compounded HT use was more common in the U.S. Southeast and Southwest (∼20%), and SSRI use was more common in the Northeast (22%) than other regions. CONCLUSION: Prescribing patterns for menopausal symptoms vary by practitioner type and U.S. region.